A Spline Smoothing Newton Method for Semi-Infinite Minimax Problems. (17th July 2014) - Dong, Li; Yu, Bo; Xiao, Yu
Abstract : Based on discretization methods for solving semi-infinite programming problems, this paper presents a spline smoothing Newton method for semi-infinite minimax problems. The spline smoothing technique uses a smooth cubic spline instead of max function and only few components in the max function are computed; that is, it introduces an active set technique, so it is more efficient for solving large-scale minimax problems arising from the discretization of semi-infinite minimax problems. Numerical tests show that the new method is very efficient.